Halo Nevi Are Not Trivial: About 2 Young Patients of Regressed Primary Melanoma That Simulates Halo Nevi - S. De Schrijver; I. Theate; O. Vanhooteghem (Case Reports in Dermatological Medicine)
Background. Halo nevi are often considered benign, and the possibility of malignancy is not always clear to practitioners. We present two case reports suggesting that a halo nevus appearance can be seen in melanoma, even in young adults. A literature search for halo nevi revealing melanoma shows that this is a very rare condition. Case presentation. This report of two young patients indicates the importance of obtaining a detailed history to detect warning signs such as itching, pain, spontaneous bleeding, and previous alterations according to the patient, including a previously totally black colour in an already fully regressed melanoma. Conclusions. The risk of a halo nevus being malignant is higher if there is only one unique halo nevus and no personal or familial history of vitiligo. We postulate that a regressing atypical nevus or a regressing melanoma may be induced by an immunologic reaction as halo nevus type of clinical picture.